Long-term outcome after colic surgery: retrospective study of 106 horses in the USA (2014–2021) - Matthews, Lisbeth B.; Sanz, Macarena; Sellon, Debra C. (Frontiers in Veterinary Science, 2023)
Objective: To determine long-term survival rate, defined as survival to 1 year after discharge from the hospital, and rate of return to prior athletic, breeding, or other function in horses undergoing colic surgery at the first presentation at one referral hospital in the Pacific northwest region of the United States. Procedures: Records were reviewed for all horses that underwent colic surgery between October 2014 and October 2021. Owners of horses that survived to discharge were contacted to obtain follow-up information via internet-based questionnaire or telephone interview. The percentage of horses that survived to one year after discharge, rates of return to function, and complications occurring after hospital discharge were determined. The possible association of patient signalment, lesion type, and surgical procedures with long-term survival was examined with Chi-square and Fisher’s exact tests. Overall satisfaction was indicated on a scale of 1 (unsatisfied) to 5 (very satisfied). Results: Of 185 horses that underwent surgical intervention for colic and met the inclusion criteria, 134 horses recovered from anesthesia, with 106 of these recovered horses (79.1%) surviving to discharge. Of the 71 horses for which follow-up information was obtained, 61 horses survived to one year after discharge (long-term survival rate of 85.9%). There were no demographic, lesion type, or surgical procedure variables significantly associated with long-term survival. Prior to surgery 59/71 horses (83.1%) were engaged in some type of athletic activity. After surgery, 44/61 horses (72.1%) were reported to be athletically active. Only one horse was reported to be retired from athletic activity as a direct result of a complication from surgery. Overall satisfaction with the decision to proceed with colic surgery was rated by all respondents as 4 or 5. Conclusions and clinical relevance: The long-term survival for this sample of horses was similar to previously published reports of long-term survival after colic surgery. Horses that survived to hospital discharge were highly likely to remain alive and be athletically active one year later. There were no factors related to the signalment of the horse, the specific cause of colic, or the surgical procedures performed that were significantly associated with likelihood of survival.